Biogeochemical technologies for managing pollution in polar ecosystems - Bashkin, V. N. (Springer, 2017)
This edited book is devoted to one of the hottest topics of modern environmental science, i.e. environmental risk management in gas industry impacted polar ecosystems of Russia. The contributions from experts cover topics that shed new light on the impacts of oil and natural gas production on arctic ecosystems in the country as well as biogeochemical engineering technologies to manage pollution in these areas. Readers will also discover new insights on potential ecological indicators for assessing geo-environmental risks of these impacted ecosystems, and climate modeling in polar areas. The book has interdisciplinary appeal, and specialists and practitioners in environmental sciences, ecology, biogeochemistry and those within the energy sector who are interested in understanding ecosystems affected by anthropogenic impacts in severe climatic conditions will find it particularly engaging. Through this book, readers will learn more about biogeochemical cycling through food chains and specific reactions of biota to environmental pollution in extreme environments through the lens of experts.- Resumé vydavatel
Keywords: biogeochemie -- arktická oblast; biogeochemie -- Rusko (federace); environmentální rizika; polární ekosystémy -- Rusko (federace); plynárenství; biogeochemistry -- Arctic region; biogeochemistry -- Russia (Federation); environmental risk; polar ecosystems -- Russia (Federation); gas industry; elektronické knihy; sborníky; electronic books; papers of several authors